Anomie of researchers in data sharing - Monteiro, Elizabete Cristina de Souza de Aguiar [UNESP] (2023)
Data sharing is standard practice in some disciplines, while in others it is particularly critical, depending on factors such as individual researchers' behavior or disciplinary culture. Anomie in data sharing can occur when the sets of cultural values that govern the researcher' conduct and institutional goals are out of balance, with cultural values or vested interests having greater relevance than institutional goals. Thus, individuals perceive themselves in disagreement with what institutions require and practice deviant behaviors, with possible data retention . The objective was to identify and discuss factors that can establish a state of anomie in researchers in the data sharing process, presenting a framework with the identified factors. The collection occurred through triangulation with the application of a questionnaire, a structured interview, and document analysis. With the documentary analysis, a framework with thirteen indexes was presented, based on the theoretical frameworks, W. Richard Scott's Institutional Theory, Icek Ajzen's Theory of Planned Behavior, and Youngseek Kim's proposed data repository sharing behavior research model. It is concluded that anomie is related to factors such as lack of clarity of laws and regulations, imbalance between institutional goals and the ways to achieve them, non-compliance with rules, and denial of morals.